INTEGRASI KURIKULUM ISMUBA DALAM MEMBENTUK ETOS KERJA PROFESIONAL SISWA: STUDI KASUS DI SMK MUHAMMADIYAH TASIKMALAYA - Andri Iskandar; Tanto Aljauharie Tantowie (As-Sulthan Journal of Education, 2026)
This study aims to explore the mechanism of the integration of the Al-Islam, Kemuhammadiyahan, and Arabic Language (ISMUBA) curriculum in shaping the professional work ethic of students at SMK Muhammadiyah Tasikmalaya. The main challenge for vocational school graduates today is the need for moral integrity and a work ethic that aligns with the demands of the industrial world. This study uses a descriptive qualitative approach with a field study method. Data were collected through in-depth interviews, observations, and documentation with research subjects including the Principal and Islamic Religious Education (PAI) teachers. The results show that the integration of the ISMUBA curriculum is implemented as a